Peran Kepala Sekolah Untuk Mengembangkan Moderasi Beragama di Lingkungan Sekolah - Efendi, Nur Mahfud; Anam, Choirul; Zainudin, Ahmad; Fathoni, Tamrin (Civiliza Publishing, Indonesia., 2024)
This study investigates the pivotal role of school principals in fostering religious moderation within educational environments. School principals are crucial in enhancing educational quality and integrating values that promote religious moderation. The research adopts a comprehensive literature review approach, gathering and analyzing relevant data on concepts, theories, and best practices related to school leadership. The study aims to explore the strategies and challenges faced by principals in implementing religious moderation and character development in schools. Findings reveal that effective school leadership, characterized by strong leadership competencies and a deep understanding of diversity values, is essential for creating an inclusive and respectful school culture. Key strategies include professional development for teachers, extracurricular programs promoting tolerance, and strong collaboration with parents and the community. However, challenges such as resistance to change, limited resources, and external pressures must be addressed through flexible policies and effective communication. The study concludes that principals play a crucial role in shaping school culture, influencing the entire school community towards embracing diversity and reducing social conflicts. Effective school leadership contributes significantly to the positive character development of students, preparing them to live harmoniously in a diverse society. This research underscores the importance of principal leadership in building inclusive and culturally respectful educational communities.